Návrh vodohospodářských opatření v malém povodí - Hlavín, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Cílem práce je návrh vodohospodářských opatření sloužících k zachycení a odvedení přívalových vod ohrožujících intravilán obce Třebařov, dále posouzení míry erozního ohrožení. Lokalita obce byla zadána vedoucím práce. Výsledkem práce je návrh průlehů.

The thesis objective is water managment measuare proposal for flood water interception and drainage which threatens Třebařov urban, next rate assessment of erosion danger. Township location was assigned by the thesis supervisor. The thesis result is proposal of furrows.
The design of the measures for flood protection in the small watershed
Keywords: GIS; eroze; vodohospodářská opatření; USLE; EUC; sklon; délka; Geographic Information System; erosion; water management measures; Universal Soil Loss Equation; Erosion Closed Unit; slope; length